Micropore Characteristics of Continental Shale in the Shan 1 Member of the Shanxi Formation and Controls on Gas Content: A Case Study of Well Quan 56, Yan’an Area - Zhao, Weiwei; Wang, Jianan; Shan, Changan; Wang, Fengqin; Sun, Jianbo; Dang, Wei; Duan, Yifei; Li, Fukang; Yang, Tianxiang (Journal of petroleum science and technology, 2023)
The continental shale with favorable geological conditions for shale gas accumulation and broad resource prospects is widely distributed in the Ordos Basin. The micropore characteristics and controls on the gas content of Shan 1 member shale reservoir were analyzed by Argon Ion Polishing-Field Emission Scanning Electron Microscopy and Nitrogen Adsorption and High-Pressure Methane Isothermal Adsorption. The results show that the shale pore types of the Shan 1 member are primarily intergranular pores and clay mineral intergranular pores, followed by micro-fractures, dissolution pores, and organic matter pores. Different pore types provide practical storage space for shale gas. The pore size distribution of the mud shale in the Shan 1 member was strongly heterogeneous. The total pore size distribution was primarily mesoporous. Mesopores account for the most pore volume, followed by macropores and micropores, which account for the total specific surface area; macropores contribute the least specific surface area. At 90 °C, the maximum adsorption capacity of methane in mud shale was 9.02~13.02 m3/t (average of 10.824 m3/t). The organic carbon content in mud shale is generally low, and the organic matter pores are relatively limited. The clay mineral pores provide important specific surface and adsorption points for methane and increased gas storage capacity. The pore network system of the shale changed from inorganic to organic with increasing degrees of thermal evolution, enhancing absorbability. The differences in pore structure characteristics in the continental shale provide reliable geological accordance for revealing the difference in gas content in the Yan’an area.